Influence of escherichia coli endotoxin-induced fever on pharmacokinetics of imidocarb in dogs and goats - Abdullah, Abdul Salam; Baggot, J. Desmond (American Veterinary Medical Association, 1984)
The pharmacokinetics of imidocarb, administered as an IV bolus dose (4 mg/kg), was studied in normal and Escherichia coli endotoxin-induced febrile dogs and goats. In the febrile group, the drug was administered 1 hour after injection of the endotoxin. The plasma and urine concentrations of imidocarb were measured by spectrophotometry. The decline in plasma drug concentrations in both species was analyzed, using a 2-compartment open model. With the exception of the coefficient A and the volume of central compartment, E coli endotoxin-induced fever produced the same changes in kinetic determinants in both species. Fever significantly decreased the distribution rate constant in both dogs (P less than 0.05) and goats (P less than 0.01). The elimination rate constant and, in turn, the half-life were not altered by the endotoxin-induced fever in either species. The volume of distribution at steady-state was significantly lower (P less than 0.01) in the febrile dogs and goats. The body clearance of imidocarb was also significantly lower in the febrile dogs (P less than 0.05) and goats (P less than 0.01). The decreased apparent volume of distribution and lower body clearance of imidocarb could explain the higher plasma values of the drug in the febrile, compared with normal, animals.